The Potential of Gingival Crevicular Fluid as a Tool for Molecular Diagnosis: A Systematic Review - CUEVAS-GONZALEZ, MARIA VERONICA (2024)
A biomarker is defined as a characteristic that is measured as an indicator of a normal biological or pathological process, a response to an exposure or intervention. Biomarkers with a diagnostic approach must identify not only the presence but also the absence of the disease with high precision, so having the biological source of the said marker is of vital importance to ensure precision and accuracy; the aim was to carry out a review of its diagnostic potential.